In the Shadow of The Birth of a Nation
XVIII, 310 p. 32 illus., 25 illus. in color.
Keywords: This collection brings together many of the world’s leading scholars on race and film to re-consider the legacy and impact of D.W. Griffith’s deeply racist 1915 epic The Birth of a Nation. While this film is often cited, there is a considerable dearth of substantial research on its initial impact and global reach. These essays fill important gaps in the history of the film, including essential work on its sources, international reception, and African American responses. This book is a key text in the history of the most infamous and controversial film ever made and offers crucial new insights to scholars and students working in film history, African American history and the history of race relations. Melvyn Stokes is Professor of Film History, University College London, UK. He is the author of D. W. Griffith’s “The Birth of a Nation”: A History of “The Most Controversial Movie of All Time” (2007) and several articles on D. W. Griffith, including “Race, Politics and Censorship: D. W. Griffith’s The Birth of a Nation in France, 1916−1923” (Cinema Journal, 2010). In 2015, he was the curator for the British Film Institute’s D. W. Griffith season. He has published 2 other books – Gilda (Palgrave/BFI, 2010) and American History through Hollywood Film (2013) – and edited a further 12 Paul McEwan is Professor of Media and Communication and Film Studies at Muhlenberg College, USA. He is the author of The Birth of a Nation (Palgrave/BFI, 2015), Cinema’s Original Sin: D. W. Griffith, American Racism, and the Rise of Film Culture (2022) and several articles and chapters on D. W. Griffith, including “The Legacy of Intolerance” in A Companion to D. W. Griffith (2018). He is also the author of Bruce McDonald’s Hard Core Logo (2011) and other essays on Canadian cinema.